Bacteriological Study for Detection The Role of Fructan Produced from Pseudomonas putida as Enhancer for Lactobacillus acidophilus Growth - Kazim, Alaa Raheem (Al-Nahrain Journal of Science, 2018)
Fructan is a kind of biopolymer produced from plants, fungi, yeast and bacteria. It is classified as prebiotics food and enhanced the growth of probiotics bacterial strains which improves the health of the individual. This article aimed to study the production and extraction of fructan from Pseudomonas putida isolated from food samples and study the effect of fructan on the viable cell number of Lactobacillus acidophilus. The results showed that Pseudomonas putida have the ability to produce fructan when cultured on production medium (YPS), fructan exhibited as white powder when extracted from YPS and the amount of fructan was 3.6 mg/100 ml, also the results showed that fructan can increase the viable cell number of Lactobacillus acidophilus when added to MRS. FTIR analysis of fructan produced from Pseudomonas putida revealed that the functional groups found in chemical structure of fructan, which it was (C-O, C-H, O-H and C=O).